An efficient, scalable approach to hydrolyze flavonoid glucuronides via activation of glycoside bond. Issue 14 (6th April 2017) - Jiang, Xue-Yang; Li, Xin-Chen; Liu, Wen-Yuan; Xu, Yun-Hui; Feng, Feng; Qu, Wei
Abstract: Hydrolyzing flavonoid glucuronides into corresponding aglycones posed some significant challenges. To improve acid-catalyzed hydrolysis process of flavonoid glucuronide, structures of glucuronide, hydrolysis parameters and post-processing were optimized. The optimized condition was performed by hydrolysis flavonoid glycoside methyl ester in a mixed solvent consisting of 2 mol/L H2 SO4 /EtOH/H2 O (1/8/1, v/v/v) at 95 °C for 7 h and resulted in up to 90% aglycone yields, minimal byproduct formations and milder hydrolysis conditions. Furthermore, the optimized method avoids tedious purification steps and is easily conducted on a relatively large-scale using economical and commercially available reagents. Graphical abstract: We developed an efficient approach to obtain scutellarein by hydrolyzing SME from methyl-esterification of scutellarin. Computational studies suggested that the methyl esterification could both accelerate the first and second steps of the acid-assisted hydrolysis process of glucuronide.